DAUR ULANG BOTOL PLASTIK MENJADI BUNGA IMITASI PADA KELOMPOK REMAJA DI LINGKUNGAN KAMPUS UNILAK - surtinah, surtinah; Lidar, Seprita; Wulantika, Trisia (SYUKUR (Jurnal Inovasi Sosial dan Pengabdian Masyarakat), 2019)
Well managed waste will improve the quality of the environment and the health of the community, recycling plastic waste by itself helps the government in managing waste, especially management is done professionally and commercially, so that it becomes a profitable business. The solutions offered from the problems faced by partners include providing training in managing waste plastic bottles into imitation flowers, and providing motivation to partners that the products will be marketed by UP2K. through the UP2K, the Unilak leadership policy will be realized to open a market monopoly to sell imitation flower bouquets and souvenirs from plastic bottles of mineral water. Output targets are articles in journals, exposure to activities in online media, increasing partner skills. The method of implementing this PKM activity is among others: Counseling, demonstration, training, mentoring, and evaluation. The results of the activities obtained were counseling about inorganic waste increasing the knowledge of participants 17% - 33%, knowledge of the benefits of used plastic bottles, after activities increased by 17% -25%, and knowledge about changing the shape of used plastic bottles to imitation flowers increased by 67% -83%.